Farnesyltransferase and geranylgeranyltransferase I: structures, mechanism, inhibitors and molecular modeling. Issue 2 (February 2015) - Shen, Mingyun; Pan, Peichen; Li, Youyong; Li, Dan; Yu, Huidong; Hou, Tingjun
Highlights Structures and therapeutic importance of FTase and GGTase-1 are briefly outlined. Available inhibitors of FTase and GGTase-1 are systematically summarized. Binding mechanisms of representative FTIs and GGTIs are described. Recent applications of molecular modeling in the design of FTIs and GGTIs are discussed.